Online Prostitution in the Perspective of Law of the Republic of Indonesia Number 44 Of 2008 On Pornography - Liza Novianti*; Waliadin Waliadin (Universitas Syiah Kuala, 2023)
Law of the Republic of Indonesia No. 44 of 2008 on pornography does not explain online prostitution service users online specifically, because positive legal arrangements in Indonesia for service users have not been effective in trapping and tackling online prostitution, in this case the law of the Republic of Indonesia No. 44 of 2008 on pornography can not ensnare service users in the field of the practice of online prostitution, so that the law of the Republic of Indonesia number 44 of 2008 on pornography only limits the parties that may be subject to sanctions, namely sanctions against service providers contained in Article 30, sanctions for server owners contained in Article 33, sanctions for commercial sex workers contained in Article 34, and sanctions for pimps contained in Article 35.